Foundations of GTK+ development - Krause, Andrew (Berkeley, Calif. Apress New York Distributed to the Book trade worldwide by Springer-Verlag New York, 2007)
Provides information on building graphical applications using GTK+.
Dr. Rowel Atienza (recommending faculty)
Keywords: GTK+.; C (Computer program language)